2018
DOI: 10.1002/ccd.27468
|View full text |Cite
|
Sign up to set email alerts
|

Validation of contemporary risk scores in predicting coronary thrombotic events and major bleeding in patients with acute coronary syndrome after drug‐eluting stent implantations

Abstract: The current three risk scores, derived and initially validated in Western populations, may not be applicable to the Chinese population, although DAPT score was determined to be a modestly accurate quantitative tool for prediction of later MB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…Our search of MEDLINE and EMBASE yielded 81 results (Figure 1). After detailed review of titles and abstracts and full manuscripts of potentially relevant papers a total of 13 studies were included 8,12‐16,18‐24 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search of MEDLINE and EMBASE yielded 81 results (Figure 1). After detailed review of titles and abstracts and full manuscripts of potentially relevant papers a total of 13 studies were included 8,12‐16,18‐24 …”
Section: Resultsmentioning
confidence: 99%
“…The case‐control study by Godschalk et al reported a C‐statistic of 0.64 for the DAPT score and very late stent thrombosis 18 . Among Chinese patients in the Song et al study, the DAPT score had poor predictive value for major adverse cardiovascular events (stent thrombosis and myocardial infarction, c‐statistic 0.53) and major bleeding (c‐statistic 0.56) 23 . The Harrell's c‐statistic for DAPT score was 0.58 for myocardial infarction and stent thrombosis and 0.49 for fatal or major bleeding from the Swedish National Registry 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Risk scores such as the prediction rule models for DAPT, the Predicting complications in Patients undergoing stent Implantation and Subsequent Dual Antiplatelet Therapy (PRECISE‐DAPT), and the Patterns of nonadherence to AntiPlatelet Regimen in Stented Patients are currently in widespread use. Nevertheless, these risk prediction models have not achieved consistent results in external validation studies . The GRACE score, as a universally recognized risk stratification tool for ischemia, has been validated in numerous studies since it was first proposed in 2004 .…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Hereafter, both the DAPT score and PARIS registry scores were retrospectively validated and compared in a Chinese population (n=5,709). 53 Only the DAPT score showed modest accuracy for predicting major bleedings. Both scores showed poor discriminative capacity predicting ischemic events.…”
Section: Patient-tailored Duration Of Dual Antiplatelet Therapymentioning
confidence: 99%